The Impact of Trade Agreements : New Approach, New Insights - Hannan, Swarnali (IMF Working Papers; Working Paper ;, 2016)
The Trans-Pacific Partnership (TPP) has reinvigorated research on the ex-ante impact of trade agreements. The results from these ex-ante models are subject to considerable uncertainties, and needs to be complimented by ex-post studies. The paper fills this gap in recent literature by employing synthetic control methods (SCM) - currently extremely popular in micro and macro studies - to understand the impact of trade agreements in the period 1983-1995 for 104 country pairs. The key advantage of using SCM to address selection bias - one of the persisting issues in trade literature - is that it allows the effect of unobserved confounder to vary with time, as opposed to traditional econometric methods that can deal with time-invariant unobserved country characteristics. Using SCM approach, the paper finds that trade agreements can generate substantial gains, on average an increase of exports by 80 percentage points over ten years. The export gains are higher when emerging markets have trade agreements with advanced markets. The paper shows that all the countries in NAFTA have substantially gained due to NAFTA. Finally, there is some evidence that trade agreements can potentially lead to slight import diversion, but not export diversion.